Low-cost transformer tester for laboratory module - Purbawa, I Made; Ardana, I Wayan Raka; Budarsa, I Gede Ketut Sri; Saputra, I Gusti Ngurah Agung Dwijaya (Proceedings; 2020: The 2nd International Conference on Applied Science and Technology (iCAST) 2019 Proceeding, 2020)
This paper presents a low-cost transformer tester for experiment module in electric machine laboratory. Unlikely the expensive transformer tester on the market, this module is built by using Arduino Uno in the hardware side, and LabView in the software side to make it less expensive. Three voltage sensors and one current sensor are used in this equipment for making some several test on transformer such as, short circuit test, open circuit test, polarity test and winding resistance test. The results of all tests can be presenting in LabView as a data and graph. The calculations are also processed in LabView using some functions on it. By using this strategy, the student will be able to learn the transformer test procedures and to compare the results of their calculations by hand with the software’s results. This module has been testing by comparing the results with the standard measuring equipment with the error for voltage and current measurements are at 0.81% and 15.29%, respectively.